National environmental policy during the Clinton years - Sheila M. Cavanagh; Robert W. Hahn; Robert N. Stavins (Fondazione Eni Enrico Mattei (FEEM), 2002)
We review major developments in national environmental policy during the Clinton Administration, defining environmental policy to include not only the statutes, regulations, and policies associated with reducing pollution, but also major issues of public lands management and species preservation. We adopt economic criteria for policy assessment — principally efficiency, cost-effectiveness, and distributional equity. While the paper is primarily descriptive, we highlight a set of themes that emerge in the economics of national environmental policy over the past decade.
Keywords: 330; environmental policy; Umweltpolitik; USA